Konsep Kearifan Lokal Dalam Pembelajaran Sejarah di SMAN 1 Galing - Etriadi (SAMBARA: Jurnal Pengabdian Kepada Masyarakat, 2024)
Local wisdom has great potential as a source of relevant and contextualized history learning for students. Historical materials do not have to be limited to textbooks, but can be obtained from the surrounding environment which is rich in local historical values. However, the enrichment of historical materials in schools, especially in public high schools, is still relatively minimal. This community service activity (PKM) aims to increase the knowledge of students and teachers at SMA Negeri 1 Galing through the integration of local wisdom as additional material in history learning. The PKM implementation method includes five stages: (1) location observation to understand the condition of the school and the number of participants, (2) confirmation with the school for scheduling activities, (3) implementation of material socialization by the team according to scientific fields, (4) evaluation through direct and indirect guidance related to the application of teaching materials, and (5) closing activities. The results of this activity showed an increase in students' and teachers' understanding of local history, and contributed to the enrichment of history subject matter in schools. Thus, local wisdom not only enriches learning materials but also strengthens students' cultural identity.